2010
DOI: 10.4306/pi.2010.7.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Korean Version of the Empathy Quotient Scale

Abstract: ObjectiveThe Empathy Quotient (EQ) is a self-reported test developed by Baron-Cohen et al. (2004) to measure the cognitive and affective aspects of empathy. The purpose of this study was to develop a Korean version of EQ and to establish its psychometric properties based on a representative Korean sample.MethodsThe Korean version of EQ and its correspondence with another popular measure of empathy, the Korean version of the Interpersonal Reactivity Index (IRI), were evaluated in a sample of 478 volunteers (156… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
4
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 22 publications
(69 reference statements)
5
48
4
11
Order By: Relevance
“…The original scale consists of 60 items (40 of them measure empathy and 20 filler items serve to distract the participants from focusing on empathy), but Lawrence et al (2004) suggested shortening the scale to 28 items loading on three factors: Cognitive Empathy (CE; 11 items), Emotional Reactivity (ER; 11 items) and Social Skills (SS; 6 items). This three-factor structure of the EQ has been partly confirmed in translated versions of the EQ in Japan (Wakabayashi et al, 2007), France (Berthoz et al, 2008), Canada (Lepage et al, 2009), Korea (Kim & Lee, 2010), Italy (Preti et al, 2011), Serbia (Dimitrijević et al, 2012) and Netherlands (Groen et al, 2015) and the scale has proven to be a valid and reliable tool for assessing empathy in both clinical and non-clinical samples.…”
Section: Introductionmentioning
confidence: 82%
“…The original scale consists of 60 items (40 of them measure empathy and 20 filler items serve to distract the participants from focusing on empathy), but Lawrence et al (2004) suggested shortening the scale to 28 items loading on three factors: Cognitive Empathy (CE; 11 items), Emotional Reactivity (ER; 11 items) and Social Skills (SS; 6 items). This three-factor structure of the EQ has been partly confirmed in translated versions of the EQ in Japan (Wakabayashi et al, 2007), France (Berthoz et al, 2008), Canada (Lepage et al, 2009), Korea (Kim & Lee, 2010), Italy (Preti et al, 2011), Serbia (Dimitrijević et al, 2012) and Netherlands (Groen et al, 2015) and the scale has proven to be a valid and reliable tool for assessing empathy in both clinical and non-clinical samples.…”
Section: Introductionmentioning
confidence: 82%
“…Empathizing involves an ability to understand other people's mental states and emotions, and be interested in the social connection with others (Kim & Lee, 2010). The ability to empathize is of particular importance for those successfully pursuing medical and clinical careers (Barak, 1990;Lambert & Barley, 2001;Hojat et al, 2002;Rosenfield & Jones, 2004).…”
Section: Empathy and Sciencementioning
confidence: 99%
“…However, no empathy measure has been validated in a pharmacy education setting in Korea, even though the Korean versions of 2 empathy measures-JSPE and IRI-were previously validated for Korean medical students. 23,24 The JSPE and JSPE-Student version (JSPE-S) are widely used as context-relevant instruments to measure the empathy of physicians and medical students with regard to patient care. 20 The IRI, however, was developed to measure empathy in the general population.…”
Section: Introductionmentioning
confidence: 99%